Resource recycling method for waste cathode carbon of electrolytic aluminum

By adopting low-acid environmental leaching and dry ball mill pre-activated treatment in the electrolytic aluminum waste cathode carbon recycling process, combined with alkali melting and neutralization and removal steps, the problems of large reagent consumption and underutilization of valuable components in the prior art are solved, and efficient and environmentally friendly resource recycling is achieved.

CN119822390AInactive Publication Date: 2025-04-15CENT SOUTH UNIV

Patent Information

Application Number
CN202510049853.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as large reagent consumption, underutilization of valuable components, serious corrosion to the equipment, and large energy consumption when recycling electrolytic aluminum waste cathode carbon.

Method used

The waste cathode carbon is leaching with a low acid environment of aluminum salt, and pre-activated by dry ball milling, combined with alkali melting and water washing and neutralization removal steps, the valuable components such as aluminum, fluorine and lithium are deeply recovered.

Benefits of technology

It realizes efficient resource recycling of electrolytic aluminum waste cathode carbon, improves recovery rate, reduces reagent consumption and energy consumption, and avoids equipment corrosion. The obtained carbon products and valuable ingredients meet the requirements of high purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005239654410000011
    Figure HDA0005239654410000011
  • Figure HDA0005239654410000021
    Figure HDA0005239654410000021
  • Figure HDA0005239654410000031
    Figure HDA0005239654410000031
Patent Text Reader

Abstract

The invention relates to an electrolytic aluminum waste cathode carbon resource recycling method which comprises the following steps: S1, mixing aluminum electrolysis waste cathode carbon with aluminum salt, and carrying out dry ball milling to obtain a ball milling material; s2, the ball-milled material is leached with an acid solution and filtered, and first-section leached residues and first-section leached liquid are obtained; s3, mixing the first-stage leaching residues with solid alkali, and roasting to obtain a sintered material; washing and filtering the sintered material to obtain second-stage filtrate and filter residues, and drying the second-stage filter residues to obtain a carbon product; and S4, adding the second-stage filtrate into the first-stage leachate until the pH value is 4.5-7.5, aging, filtering to obtain a third-stage leachate and third-stage filter residues, and roasting the third-stage filter residues to obtain an aluminum-fluorine product. According to the method, the waste cathode carbon is leached in the aluminum salt low-acid environment, the reaction environment is milder, and meanwhile the leaching efficiency is not reduced. And through further low-temperature alkali fused salt roasting, fluoride in the waste cathode carbon is removed, and the purity of the obtained carbon product is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of comprehensive utilization of solid waste from electrolytic aluminum industry, and relates to a method for resource recovery of waste cathode carbon from electrolytic aluminum. Background Art

[0002] Waste cathode carbon blocks are mainly graphite cathodes corroded by electrolytes and a small amount of slot linings. The main component is highly graphitized carbon, with a content of about 40%-60%, as well as some fluorides and aluminum compounds, basically in the form of cryolite, sodium fluoride, calcium fluoride, aluminum oxide, aluminum nitride, and trace amounts of aluminum silicates and cyanides. The composition of waste cathode carbon blocks is complex and highly toxic, but there are also many valuable components, which are suitable for resource processing and have certain commercial value. The large amount of highly graphitized carbon in waste cathode carbon blocks is the source of its main recovery value. In addition, the fluoride in the waste cathode is not only a harmful substance, but can be used as a valuable component. In addition to the above two types of valuable components, the waste cathode also contains a certain amount of lithium salts.

[0003] Prior art CN111232947B discloses a method for recovering waste cathode carbon blocks from aluminum electrolysis, comprising the following steps:

[0004] (1) crushing and screening the waste cathode carbon blocks to obtain carbon particles; (2) mixing the carbon particles with sulfuric acid solution to obtain slurry A, and then pressurizing and leaching to obtain slurry B; (3) evaporating and concentrating slurry B to a water content of less than 8% by mass to obtain slurry C; (4) adding concentrated sulfuric acid to slurry C to obtain slurry D, and then roasting at 150-300°C for 0.5-10 hours, and then roasting at 300-600°C for 0.5-8 hours to obtain roasted carbon; (5) mixing the roasted carbon with a leaching agent for leaching, filtering and washing to obtain purified carbon. However, it ignores the recovery of lithium, and a large amount of harmful hydrogen fluoride gas will be generated in the concentrated sulfuric acid system.

[0005] Prior art CN110407190B discloses a method for recovering carbon from waste cathodes of aluminum electrolysis, comprising the following steps: Step 1, crushing the waste cathode carbon blocks of aluminum electrolysis cells to obtain spare particles; Step 2, mixing the spare particles obtained in step 1 with solid alkali evenly, adding deionized water, standing and evaporating to remove water, and obtaining a mixture; Step 3, heating the mixture obtained in step 2 to 320-700°C in a protective atmosphere, keeping the temperature for 0.5-4h, washing with water to neutrality after cooling, filtering and drying to obtain alkaline slag; Step 4, adding the alkaline slag obtained in step 3 to a mixed solution of acid and sodium fluoride for leaching, filtering after leaching, washing with water to neutrality, and obtaining carbon powder. However, the prior art only recovers carbon powder, and the recovery of other valuable components is insufficient, and the alkaline slag is leached with a mixed solution of acid and sodium fluoride, which is costly.

[0006] Prior art CN118359193A discloses a method for preparing high-purity graphite by dissolving waste cathode with aluminum salt in coordination with ultrasonic enhanced dissolution, wherein the waste cathode of aluminum electrolysis is crushed and screened to obtain waste cathode particles, the waste cathode particles are added to an aluminum salt solution, and stirred at a temperature of 30 to 90°C for 10 to 60 minutes to obtain a mixed solution; the pH value of the mixed solution is adjusted to 0 to 2.5 for ultrasonic enhanced dissolution for 0.5 to 3 hours, solid-liquid separation is performed to obtain filtrate I and filter residue I, and filter residue I is dried to obtain high-purity graphite carbon powder; the pH value of filtrate I is adjusted to 8 to 11 for precipitation reaction for 0.5 to 4 hours, and solid-liquid separation is performed to obtain filtrate II and cryolite. However, the prior art is to prepare high-purity graphite by ultrasonic enhanced aluminum salt dissolution of waste cathode, which has high requirements for equipment.

[0007] The prior art CN117735578A discloses that the overhaul slag is mixed with the reactant and the reaction aid, and then sintered at a high temperature of 550-1000°C, and the sintered material is leached with water to obtain a leachate containing elements such as F, Al, Na, and Li; by adjusting the pH value of the leachate, the reaction is controlled to generate cryolite crystals and aluminum hydroxide crystals in sequence, and after solid-liquid separation, a purified solution is obtained, and after evaporation and concentration of the purified solution, sodium carbonate is added to react to obtain a lithium carbonate product. However, the high-temperature sintering treatment of the waste cathode without adding a protective atmosphere will result in direct combustion and waste of carbon, and it is not environmentally friendly.

[0008] It can be seen that the existing waste cathode recycling process still has many problems such as large reagent consumption, insufficient utilization of valuable components, serious corrosion to equipment, and high energy consumption. Summary of the invention

[0009] The purpose of the present invention is to provide a method for resource recovery of waste cathode carbon from electrolytic aluminum, so as to recover the main valuable components and improve the recovery rate at the same time.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A method for recycling waste cathode carbon from electrolytic aluminum, comprising the following steps:

[0012] S1, mixing the waste cathode carbon from aluminum electrolysis with aluminum salt, and dry-milling the mixture to obtain a ball mill material;

[0013] S2, leaching the ball mill material with an acid solution, filtering, and obtaining a section of leached residue and a section of leached liquid;

[0014] S3, mixing the first-stage leaching residue with solid alkali and roasting them to obtain a sintering material; washing the sintering material with water, filtering it to obtain a second-stage filtrate and a second-stage filter residue, and drying the second-stage filter residue to obtain a carbon product;

[0015] S4, adding the second stage filtrate to the first stage leaching solution until the pH is 4.5-7.5, aging and filtering to obtain the third stage leaching solution and the third stage filter residue, and the third stage filter residue is roasted to obtain the aluminum fluoride product;

[0016] S5, adding the first purifier to the three-stage leaching solution until the pH is 10-12, removing the precipitate, then adding the second purifier, and then removing the precipitate to obtain a purified solution;

[0017] S6. The purified liquid is evaporated and concentrated, cooled and crystallized to obtain a lithium-rich liquid; sodium carbonate is added to the lithium-rich liquid to recover lithium carbonate.

[0018] In one of the preferred embodiments, the aluminum electrolysis waste cathode carbon is crushed and then mixed with aluminum salt, and the particle size of the crushed aluminum electrolysis waste cathode carbon is 100-300 mesh.

[0019] In one preferred embodiment, the spent cathode carbon from aluminum electrolysis includes, by weight, 60-80 parts of carbon, 5-10 parts of fluorine, 4-10 parts of sodium, 3-6 parts of aluminum, 0.5-1.5 parts of lithium, 0.1-0.3 parts of calcium, 0.1-0.3 parts of silicon, and 0.3-0.6 parts of iron.

[0020] In one preferred embodiment, in step S1, the aluminum salt is one of Al2(SO4)3, Al(NO3)3, and AlCl3.

[0021] In one of the preferred embodiments, in step S1, the fluorine-aluminum ratio in the material after the waste cathode carbon from aluminum electrolysis is mixed with aluminum salt is 3:1-1:1.

[0022] Within this fluorine-aluminum ratio range, the complex phase of aluminum and fluorine can exist stably, so that the fluorine in the spent cathode enters the liquid phase without generating hydrogen fluoride for volatilization. If the ratio is too large or too small, the complex phase will be unstable, resulting in a decrease in the fluorine recovery rate.

[0023] In one preferred embodiment, in step S1, the ball-to-material ratio of dry ball milling is 5:1-15:1, the dry ball milling speed is 300-500 r / min, and the dry ball milling time is 2-6 h.

[0024] The present invention uses dry ball milling as a pre-activation treatment before leaching.

[0025] Pre-activation treatment is beneficial to improving the physical separation degree of non-carbon phase, increasing the mixing degree of spent cathode carbon and aluminum salt, and improving the reaction activity of aluminum salt.

[0026] In a preferred embodiment, in step S2, the acid solution is one of dilute sulfuric acid, dilute nitric acid and dilute hydrochloric acid.

[0027] In one preferred embodiment, in step S2, the concentration of the acid solution is 0.01-0.5 mol / L.

[0028] Too high acid concentration will cause the entire leaching process to be dominated by acid, making aluminum salt an auxiliary leaching agent, which will cause a large amount of hydrogen fluoride to be released.

[0029] In one preferred embodiment, in step S2, the liquid-solid ratio of leaching is 5:1-14:1, the leaching temperature is 70-100°C, and the leaching time is 0.5-2.5h.

[0030] Under this condition, fluorine and aluminum can be well complexed, so that lithium can be leached out.

[0031] During the leaching process in step S2, the complex fluorides in the spent cathode react with the aluminum ions in the solution. The main reactions are as follows:

[0032] Na3AlF6+2Al 3+ =3Na + +3AlF2 + ;

[0033] CaF2+Al 3+ =Ca 2+ +AlF2 + ;

[0034] 2LiF+Al 3+ =2Li + +AlF2 + .

[0035] Fluorine is removed by the leaching process in step S2.

[0036] In a preferred embodiment, in step S3, the solid base is at least two of NaOH, KOH and Na2CO3.

[0037] The composite alkali molten salt has a better protective effect on carbon and requires a lower melting temperature.

[0038] In one preferred embodiment, in step S3, the mass ratio of the first-stage leaching residue to the solid alkali is 1:1-1:3.

[0039] Sufficient alkali can better coat the carbon and promote the decomposition of insoluble impurities.

[0040] In one preferred embodiment, in step S3, the calcination temperature is 350-550° C., and the calcination time is 1-3 h.

[0041] Too high a temperature and too long a time will result in a large amount of charcoal combustion loss.

[0042] In one preferred embodiment, in step S3, the sintering material is crushed before washing, and the particle size of the crushed sintering material is 50-200 mesh.

[0043] During the roasting process, the insoluble impurities remaining in the first-stage leaching slag are decomposed in the molten salt environment and converted into soluble fluorides. The main reactions are as follows:

[0044] Na3AlF6+4NaOH=NaAlO2+6NaF+2H2O;

[0045] Na3AlF6+4KOH=KAlO2+3NaF+3KF+2H2O;

[0046] Na3AlF6+2Na2CO3=NaAlO2+6NaF+2CO2(g);

[0047] Al2SiO5+4NaOH=Na2SiO3+2NaAlO2+2H2O.

[0048] In one of the preferred embodiments, in step S3, the liquid-solid ratio of water washing is 2:1-8:1, the water washing time is 10-90 min, and the water washing temperature is 20-50° C. This process can better remove the residual fluoride in the carbon.

[0049] In one preferred embodiment, in step S4, the aging time is 2-4 hours.

[0050] In the step S4, the filter residue obtained after aging and filtration is mainly hydroxyaluminum fluoride.

[0051] In one preferred embodiment, in step S4, the temperature of the three-stage filter residue calcination is 400-600° C., and the calcination time is 1-3 hours.

[0052] After three-stage calcination of the filter residue, the fluorine aluminum product obtained is mainly a mixture of AlF3 and Al2O3.

[0053] In one preferred embodiment, in step S5, the first purifier is Ca(OH)2.

[0054] In step S5, Ca(OH)2 is added at a pH of 10-12 to deeply remove excess fluoride and aluminum ions.

[0055] In one preferred embodiment, in step S5, the second purifier is Na2CO3.

[0056] In step S5, Na2CO3 is added to remove excess calcium ions.

[0057] In one preferred embodiment, in step S5, the ratio of the added molar amount of the second purifier to the calcium ions is 1-1.3:1.

[0058] In one preferred embodiment, in step S6, the concentration of lithium ions in the solution after evaporation and concentration is 19-22 g / L.

[0059] In one preferred embodiment, in step S6, the temperature of cooling crystallization is 0-5°C.

[0060] Cooling crystallization is to remove sodium salt.

[0061] In one preferred embodiment, in step S6, the temperature when sodium carbonate is added to the lithium-rich solution is 80-100°C.

[0062] In one preferred embodiment, in step S6, the molar amount of sodium carbonate added is 1.1-1.3 times that of lithium ions.

[0063] In one preferred embodiment, in step S6, the obtained lithium carbonate is washed 2-3 times with hot water at 90-100° C. to remove soluble impurities, and the liquid-to-solid ratio of the washing is 1:1-3:1.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] (1) In the present invention, by ball-milling and activating the spent cathode carbon from aluminum electrolysis with aluminum salt, it is beneficial to improve the physical separation degree of the non-carbon phase, increase the mixing uniformity and reaction contact area of ​​the spent cathode carbon and the aluminum salt, and promote the conversion of the aluminum salt into a highly reactive aluminum salt, thereby achieving an enhanced effect on the leaching process of the spent cathode carbon.

[0066] (2) The present invention makes full use of the toxic hazardous waste aluminum electrolysis cathode carbon. The recovered high-purity carbon product can be used to make aluminum electrolysis cathode or battery negative electrode. The aluminum fluoride product can be returned to the electrolytic cell. The lithium carbonate is used as a raw material for lithium batteries in the new energy industry, thus finding a technical path to maximize the value of aluminum electrolysis waste cathode resources.

[0067] (3) The present invention uses aluminum salt low-acid environment to leach waste cathode carbon. Compared with the traditional strong acid and strong alkali leaching method, the reaction environment is milder, and the leaching efficiency is not reduced, avoiding the corrosion damage of the strong acid and strong alkaline system to the equipment. At the same time, it can also achieve full leaching of the waste cathode carbon through low concentration acid. Through further alkaline molten salt roasting, the fluoride in the waste cathode carbon is further removed, which can ensure the high purity of the obtained carbon product, and the various indicators of leaching toxicity meet the standard requirements.

[0068] (4) The present invention adds a second-stage leaching solution to the first-stage leaching solution, that is, uses an alkali-melting water wash solution to neutralize the aluminum salt leaching solution, which can improve the recovery rate of aluminum and fluorine and reduce the waste of valuable components. The alkali-melting water wash solution not only plays a role in improving the purity of the carbon product, but also plays a role in adjusting the pH to recover aluminum and fluorine.

[0069] In summary, the steps of the present invention are interrelated and interdependent, and the overall logic of aluminum salt leaching-alkali melting-neutralization and impurity removal-deep impurity removal-lithium precipitation is adopted. For example, the aluminum salt leaching of step S2 is carried out in an acidic environment. The present invention uses the leached slag after aluminum salt leaching for alkali melting and water washing. If the order is reversed, the waste cathode carbon of aluminum electrolysis is first washed with alkali melting water, and the subsequent steps need to use an acid far greater than the amount used in the method of the present invention to adjust the pH to acidity before the next step of treatment. In this way, the workload and cost will be greatly increased. Similarly, the other steps are similar, such as reversing the order of steps or removing one or more other steps, which will bring obvious adverse effects. For example, in the subsequent impurity removal process of the leachate, neutralization is first used to initially remove aluminum and fluorine, which can effectively recover and reduce the consumption of subsequent purifiers. Calcium hydroxide is used to further remove fluorine, which will introduce calcium ions, and the sodium carbonate in the next step can remove calcium ions. Then the aluminum, fluorine, and calcium in the solution are removed to obtain a high-purity lithium carbonate product. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 The present invention is a schematic flow chart of the method for recycling waste cathode carbon from aluminum electrolysis;

[0071] Figure 2 is the XRD spectrum of the aluminum electrolysis waste cathode carbon used in Example 1;

[0072] Figure 3 This is the XRD pattern of the carbon product obtained in Example 1. DETAILED DESCRIPTION

[0073] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention by adopting other various specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made by adopting the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. The test methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, it is carried out according to the general international standards, conventional conditions, or according to the conditions recommended by the manufacturer.

[0074] In the embodiment of the present invention, the main element contents in the aluminum electrolysis waste cathode carbon are 73.22% C, 7.49% F, 6.62% Na, 4.28% Al, 1.03% Li, 0.20% Ca, 0.23% Si, and 0.44% Fe.

[0075] In the embodiments of the present invention, chemical analysis experiments were carried out on the original samples and the treated products, including XRF, XRD, carbon content test, ion chromatography test, and ion selective electrode concentration test, to confirm the changes in key elements (F, C, Al, Li), components and fluoride leaching concentrations.

[0076] Example 1

[0077] like Figure 1 As shown, this embodiment provides a method for recycling waste cathode carbon from aluminum electrolysis, the method comprising:

[0078] S1. Crushing the waste cathode carbon from aluminum electrolysis to obtain crushed material, wherein the crushed particle size of the waste cathode carbon from aluminum electrolysis is 200 meshes.

[0079] S2, mixing the crushed material with aluminum salt powder, and performing pre-activation treatment by ball mill dry grinding to obtain ball mill material;

[0080] The aluminum salt powder is Al2(SO4)3. After the aluminum salt is added, the fluorine-aluminum ratio in the mixed material is 1.3:1. The ball-to-material ratio of the ball milling pre-activation treatment is 10:1, the ball milling speed is 300r / min, and the ball milling time is 4h.

[0081] S3, leaching the ball mill with a low concentration acid solution, stirring the leaching to leach out the fluoride, and then filtering to obtain a section of leached residue and a section of leaching liquid;

[0082] The low-concentration acid solution is 0.01 mol / L dilute sulfuric acid, the liquid-to-solid ratio is 10:1, the temperature during the leaching process is 90° C., and the leaching time is 0.5 h.

[0083] S4, mixing the first-stage leaching residue with solid alkali, roasting for a certain period of time, and crushing after cooling to obtain a sintering material;

[0084] The solid alkali is a mixture of NaOH and KOH in a mass ratio of 1:1, the mass ratio of the first-stage leaching residue and the solid alkali is 1:1.5, the roasting temperature is 400°C, the roasting time is 2h, and the crushing particle size of the sintered material is 150 mesh.

[0085] S5, leaching the sintered material with water and filtering to obtain a second-stage leaching solution, and drying the filter residue to obtain a carbon product;

[0086] The liquid-to-solid ratio of the water leaching process was 3:1, the leaching time was 20 min, and the leaching temperature was 25 °C.

[0087] S6, adding the second stage leachate to the first stage leachate to a first target pH, filtering after aging to obtain the third stage leachate, and roasting the filter residue to obtain an aluminum fluoride product;

[0088] The first target pH is 5.5, the aging time is 2 hours, the obtained filter residue is mainly hydroxyaluminum fluoride, the filter residue calcination temperature is 500°C, the calcination time is 1.5 hours, and the obtained fluoroaluminum product is mainly a mixture of AlF3 and Al2O3.

[0089] S7, adding a first purifier to the three-stage leachate to a second target pH, removing the precipitate, and then adding a second purifier to remove the precipitate to obtain a purified solution;

[0090] The first purifier is a Ca(OH)2 suspension, the second target pH is 11, and excess fluorine and aluminum ions are removed. The second purifier is Na2CO3, which removes excess calcium ions, and the added molar ratio to calcium ions is 1.1.

[0091] S8. The purified liquid is evaporated and concentrated, and then the concentrated liquid is cooled and crystallized to remove the sodium salt, and then sodium carbonate is added to the lithium-rich liquid to recover lithium carbonate, and the filtered lithium carbonate is washed with water to remove soluble impurities.

[0092] After evaporation and concentration, the lithium concentration in the solution is 20g / L. The temperature of the concentrated solution for cooling and crystallizing to remove sodium salt is 0°C. The temperature when sodium carbonate is added is 90°C. The molar amount of sodium carbonate added is related to the amount of lithium ions, with an excess of 10%. The filtered lithium carbonate is washed twice with 100°C hot water to remove soluble impurities, and the liquid-to-solid ratio of the washing is 2:1.

[0093] The carbon content of the obtained carbon product is 99.24%, the fluorine recovery rate is 89.81%, the purity of the lithium carbonate product is 99.09%, and the lithium recovery rate is 92.70%. The XRD test of the aluminum electrolysis waste cathode carbon is as follows: Figure 2 As shown; the obtained carbon product was subjected to XRD detection, and its spectrum is as shown Figure 3 shown.

[0094] Example 2

[0095] like Figure 1 As shown, this embodiment provides a method for recycling waste cathode carbon from aluminum electrolysis, the method comprising:

[0096] S1. Crushing the waste cathode carbon from aluminum electrolysis to obtain crushed material, wherein the crushed particle size of the waste cathode carbon from aluminum electrolysis is 150 meshes.

[0097] S2, mixing the crushed material with aluminum salt powder, and performing pre-activation treatment by ball mill dry grinding to obtain ball mill material;

[0098] The aluminum salt powder is Al(NO3)3. After the aluminum salt is added, the fluorine-aluminum ratio in the mixed material is 1.5:1. The ball-to-material ratio of the ball milling pre-activation treatment is 10:1, the ball milling speed is 300r / min, and the ball milling time is 4h.

[0099] S3, leaching the ball mill with a low concentration acid solution, stirring the leaching to leach out the fluoride, and then filtering to obtain a section of leached residue and a section of leaching liquid;

[0100] The low-concentration acid solution is 0.35 mol / L dilute nitric acid, the liquid-to-solid ratio is 8:1, the temperature during the leaching process is 90° C., and the leaching time is 2 hours.

[0101] S4, mixing the first-stage leaching residue with solid alkali, roasting for a certain period of time, and crushing after cooling to obtain a sintering material;

[0102] The solid alkali is a mixture of NaOH and Na2CO3 in a mass ratio of 1.5:1, the mass ratio of the first-stage leaching residue and the solid alkali is 1:1.5, the roasting temperature is 550°C, the roasting time is 2h, and the crushing particle size of the sintered material is 150 mesh.

[0103] S5, leaching the sintered material with water and filtering to obtain a second-stage leaching solution, and drying the filter residue to obtain a carbon product;

[0104] The liquid-to-solid ratio of the water leaching process was 5:1, the leaching time was 20 min, and the leaching temperature was 45 °C.

[0105] S6, adding the second stage leachate to the first stage leachate to a first target pH, filtering after aging to obtain the third stage leachate, and roasting the filter residue to obtain an aluminum fluoride product;

[0106] The first target pH is 6, the aging time is 2 hours, the obtained filter residue is mainly hydroxyaluminum fluoride, the filter residue calcination temperature is 500°C, the calcination time is 2 hours, and the obtained fluoroaluminum product is mainly a mixture of AlF3 and Al2O3.

[0107] S7, adding a first purifier to the three-stage leachate to a second target pH, removing the precipitate, and then adding a second purifier to remove the precipitate to obtain a purified solution;

[0108] The first purifier is a Ca(OH)2 suspension, the second target pH is 11, and excess fluorine and aluminum ions are removed. The second purifier is Na2CO3, which removes excess calcium ions, and the ratio of the added molar amount to the amount of calcium ions is 1.1:1.

[0109] S8. The purified liquid is evaporated and concentrated, and then the concentrated liquid is cooled and crystallized to remove the sodium salt, and then sodium carbonate is added to the lithium-rich liquid to recover lithium carbonate, and the filtered lithium carbonate is washed with water to remove soluble impurities.

[0110] After evaporation and concentration, the lithium concentration in the solution is 20g / L. The temperature of cooling and crystallizing the concentrated solution to remove sodium salt is 0°C. The temperature when sodium carbonate is added is 90°C. The molar amount of sodium carbonate added is related to the amount of lithium ions, and the excess is 10%. The filtered lithium carbonate is washed twice with hot water at 100°C to remove soluble impurities, and the liquid-to-solid ratio is 2:1.

[0111] The carbon content of the obtained carbon product is 98.93%, the fluorine recovery rate is 91.27%, the purity of the lithium carbonate product is 99.31%, and the lithium recovery rate is 93.23%.

[0112] Example 3

[0113] like Figure 1 As shown, this embodiment provides a method for recycling waste cathode carbon from aluminum electrolysis, the method comprising:

[0114] S1. Crushing the waste cathode carbon from aluminum electrolysis to obtain crushed material, wherein the crushed particle size of the waste cathode carbon from aluminum electrolysis is 250 meshes.

[0115] S2, mixing the crushed material with aluminum salt powder, and performing pre-activation treatment by ball mill dry grinding to obtain ball mill material;

[0116] The aluminum salt powder is Al(NO3)3. After the aluminum salt is added, the fluorine-aluminum ratio in the mixed material is 3:1. The ball-to-material ratio of the ball milling pre-activation treatment is 15:1, the ball milling speed is 300r / min, and the ball milling time is 5h.

[0117] S3, leaching the ball mill with a low concentration acid solution, stirring the leaching to leach out the fluoride, and then filtering to obtain a section of leached residue and a section of leaching liquid;

[0118] The low-concentration acid solution is 0.25 mol / L dilute nitric acid, the liquid-to-solid ratio is 14:1, the temperature during the leaching process is 90° C., and the leaching time is 2 hours.

[0119] S4, mixing the first-stage leaching residue with solid alkali, roasting for a certain period of time, and crushing after cooling to obtain a sintering material;

[0120] The solid alkali is a mixture of NaOH and Na2CO3 in a mass ratio of 2:1, the mass ratio of the first-stage leaching residue and the solid alkali is 1:3, the roasting temperature is 450°C, the roasting time is 2h, and the crushing particle size of the sintered material is 150 mesh.

[0121] S5, leaching the sintered material with water and filtering to obtain a second-stage leaching solution, and drying the filter residue to obtain a carbon product;

[0122] The liquid-to-solid ratio of the water leaching process was 8:1, the leaching time was 20 min, and the leaching temperature was 60 °C.

[0123] S6, adding the second stage leachate to the first stage leachate to a first target pH, filtering after aging to obtain the third stage leachate, and roasting the filter residue to obtain an aluminum fluoride product;

[0124] The first target pH is 5, the aging time is 2 hours, the obtained filter residue is mainly hydroxyaluminum fluoride, the filter residue calcination temperature is 500°C, the calcination time is 2 hours, and the obtained fluoroaluminum product is mainly a mixture of AlF3 and Al2O3.

[0125] S7, adding a first purifier to the three-stage leachate to a second target pH, removing the precipitate, and then adding a second purifier to remove the precipitate to obtain a purified solution;

[0126] The first purifier is a Ca(OH)2 suspension, the second target pH is 11, and excess fluorine and aluminum ions are removed. The second purifier is Na2CO3, which removes excess calcium ions, and the ratio of the added molar amount to the amount of calcium ions is 1.1.

[0127] S8. The purified liquid is evaporated and concentrated, and then the concentrated liquid is cooled and crystallized to remove the sodium salt, and then sodium carbonate is added to the lithium-rich liquid to recover lithium carbonate, and the filtered lithium carbonate is washed with water to remove soluble impurities.

[0128] The target lithium concentration of the evaporation concentration process is 20 g / L, the temperature of cooling and crystallizing the concentrated solution to remove sodium salt is 0°C, and the temperature when sodium carbonate is added is 90°C. The molar amount of sodium carbonate added is related to the amount of lithium ions, and the excess is 10%. The filtered lithium carbonate is washed twice with hot water at 100°C to remove soluble impurities, and the liquid-to-solid ratio is 2:1.

[0129] The carbon content of the obtained carbon product is 99.07%, the fluorine recovery rate is 90.59%, the purity of the lithium carbonate product is 98.37%, and the lithium recovery rate is 90.65%.

[0130] Comparative Example 1

[0131] On the basis of Example 1, the step of pre-activation by ball milling of S2 aluminum salt was removed, and the crushed material was directly leached with the low-concentration acid solution of S3. Other conditions were the same as in Example 1.

[0132] The results showed that hydrogen fluoride gas was generated in S3, the lithium leaching rate was 78.35%, the carbon content of the final carbon product was 90.33%, the fluorine recovery rate was 83.45%, the purity of the lithium carbonate product was 98.13%, and the lithium recovery rate was 83.77%. It can be seen that aluminum salt leaching can stably and efficiently leach fluoride from the spent cathode.

[0133] Comparative Example 2

[0134] On the basis of Example 1, the step of pre-activation of S2 aluminum salt by ball milling was removed, and the crushed material and aluminum salt were simply mixed and then leached in a low-concentration acid solution. Other conditions were the same as in Example 1.

[0135] The results showed that the carbon content of the final carbon product was 95.84%, the fluorine recovery rate was 89.91%, the purity of the lithium carbonate product was 98.41%, and the lithium recovery rate was 88.70%. It can be seen that ball milling pre-activation can enhance the effect of aluminum salt leaching.

[0136] Comparative Example 3

[0137] On the basis of Example 1, the S4 roasting process is removed, and an alkaline solution containing an equal mass of alkali is directly used to leach a section of leached residue, and other conditions are the same as in Example 1.

[0138] The results showed that the carbon content of the final carbon product was 89.65%, the fluorine recovery rate was 84.33%, the purity of the lithium carbonate product was 98.86%, and the lithium recovery rate was 85.32%. It can be seen that the effect of alkali fusion purification of carbon materials is better than that of alkali leaching.

[0139] Comparative Example 4

[0140] On the basis of Example 1, in step S6, instead of adding the second-stage leaching solution, a 2 mol / L NaOH solution is added to the first target pH, i.e., 11. Other conditions are the same as in Example 1.

[0141] The results showed that the carbon content of the final carbon product was 99.01%, the fluorine recovery rate was 79.84%, the purity of the lithium carbonate product was 99.11%, and the lithium recovery rate was 83.74%. It can be seen that not reusing the second-stage filtrate will lead to a large amount of fluorine being wasted, and the fluorine-containing waste liquid generated needs further treatment.

[0142] Comparative Example 5

[0143] Referring to the prior art CN 111232947 B, the specific operation is as follows:

[0144] (1) Crush and screen the cathode carbon block to obtain 200-mesh carbon particles;

[0145] (2) Taking the Si element in the carbon particles and the S element in the sulfuric acid solution as the target, the molar ratio of Si to S in slurry A is 1:2.10 after adding the sulfuric acid solution. The concentration of the sulfuric acid solution is 3 mol / L, the immersion time is 5 hours, the temperature is 150°C, and the pressure is 0.4 MPa. The gas generated in the process is absorbed by alkaline solution.

[0146] (3) Slurry B was evaporated and concentrated at a temperature of 120° C. to obtain slurry C having a water content of 8% by mass. The generated steam was collected to obtain slurry C.

[0147] (4) The F element in slurry C and the concentrated sulfuric acid and the sulfur element in slurry C are targeted. After adding concentrated sulfuric acid, the molar ratio of F to S in slurry D is 1:1.0. The concentration of the concentrated sulfuric acid is 18.4 mol / L. Then, the slurry is roasted at 150°C for 5 hours, which is the first stage of roasting. The flue gas generated in the process is absorbed and recovered by alumina dry method. After that, the slurry is roasted at 350°C for 3 hours, which is the second stage of roasting. The roasted charcoal is obtained and the generated flue gas is recovered. The recovery rate of fluorine is 83.14%.

[0148] (5) The roasted charcoal and the leaching agent are mixed and leached in a ratio of 1 g: 1 ml, wherein the leaching agent is a mixed solution of water and a pH regulator M sulfuric acid, the leaching temperature is 70° C., the leaching time is 1 hour, and during the leaching process, the pH is adjusted by adding a pH regulator sulfuric acid to obtain a slurry E with a pH of 2; the slurry E is filtered and washed to obtain a neutral filter cake, and the filter cake is dried to obtain a carbon material with a purity of 98.52%.

[0149] There are a lot of lithium and aluminum in the filtrate, but the filtrate composition is complex, the valuable components are difficult to separate and difficult to recover. The subsequent treatment of the filtrate is difficult. At the same time, a large amount of hydrogen fluoride gas is generated during the comparative example process.

[0150] Comparative Example 6

[0151] Reference CN110407190B

[0152] Take 10g of waste cathode carbon blocks from an aluminum electrolytic cell of a domestic factory, crush them to -200 mesh, accounting for 90%, mix them evenly with NaOH at a mass ratio of 1:1.7, add 20g of deionized water and 1ml of alcohol in turn, and let them stand and soak for 4h.

[0153] After standing and impregnating, the mixture of the spent cathode slurry is evaporated and dehydrated and placed in a corundum crucible, and alkali-melted at 550°C in a nitrogen atmosphere in a muffle furnace for 2 hours; the cooled alkali-melted slag is washed with water with the assistance of an ultrasonic power of 900 W until the solution is neutral, and the washed slag is filtered and dried.

[0154] The alkali-soaked slag was subjected to ultrasonic-assisted acid leaching in hydrochloric acid + sodium fluoride solution to remove impurities. The ultrasonic power of the acid leaching was 900 W, the temperature was 70 ° C, the time was 2 h, the liquid-to-solid ratio was 10:1, and the H + The concentration is 4 mol / L and the NaF concentration is 10 g / L. After acid leaching, it is washed with water until neutral, filtered, and the filter residue is dried to obtain carbon powder with a purity of 99.36%.

[0155] There are a lot of lithium, aluminum and fluorine in the washing liquid, but its composition is complex, the valuable components are difficult to separate and recover, and subsequent treatment is difficult.

[0156] As can be seen from the results of the embodiments, the method provided by the present invention can recover valuable lithium, aluminum, fluorine and carbon in the waste cathode carbon of aluminum electrolysis in the form of lithium carbonate, aluminum fluoride, aluminum oxide and carbon, respectively, thereby realizing high added value and full quantitative utilization of the waste cathode carbon.

[0157] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for recycling waste cathode carbon from electrolytic aluminum, characterized in that: The steps include: S1, mixing the waste cathode carbon from aluminum electrolysis with aluminum salt, and dry-milling the mixture to obtain a ball mill material; S2, leaching the ball mill material with an acid solution, filtering, and obtaining a section of leached residue and a section of leached liquid; S3, mixing the first-stage leaching residue with solid alkali and then roasting to obtain a sintering material; The sintered material is then washed with water and filtered to obtain a second-stage filtrate and a second-stage filter residue, and the second-stage filter residue is dried to obtain a carbon product; S4, adding the second stage filtrate to the first stage leaching solution until the pH is 4.5-7.5, aging and filtering to obtain the third stage leaching solution and the third stage filter residue, and the third stage filter residue is roasted to obtain the aluminum fluoride product; S5, adding the first purifier to the three-stage leaching solution until the pH is 10-12, removing the precipitate, then adding the second purifier, and then removing the precipitate to obtain a purified solution; S6, evaporating and concentrating the purified liquid, cooling and crystallizing it to obtain a lithium-rich liquid; Sodium carbonate is added to the lithium-rich solution to recover lithium carbonate.

2. The method according to claim 1, characterized in that The spent cathode carbon from aluminum electrolysis includes 60-80 parts of carbon, 5-10 parts of fluorine, 4-10 parts of sodium, 3-6 parts of aluminum, 0.5-1.5 parts of lithium, 0.1-0.3 parts of calcium, 0.1-0.3 parts of silicon, and 0.3-0.6 parts of iron.

3. The method according to claim 1, characterized in that In step S1, the aluminum salt is Al2(SO4)3, At least one of Al(NO3)3, AlCl3.

4. The method according to claim 1, characterized in that: In the step S1, the fluorine-aluminum ratio in the material after the waste cathode carbon from aluminum electrolysis is mixed with the aluminum salt is 3:1-1:

1.

5. The method according to claim 1, characterized in that: In step S2, the acid solution is dilute sulfuric acid, One of dilute nitric acid and dilute hydrochloric acid; the concentration of the acid solution is 0.01-0.5 mol / L.

6. The method according to claim 1, characterized in that In step S2, the liquid-solid ratio of leaching is 5:1-14:1, the leaching temperature is 70-100° C., and the leaching time is 0.5-2.5 h.

7. The method according to claim 1, characterized in that In the step S3, the solid alkali is at least two of NaOH, KOH and Na2CO3; the mass ratio of the first-stage leaching residue to the solid alkali is 1:1-1:3; the roasting temperature is 350-550°C, and the roasting time is 1-3h.

8. The method according to claim 1, characterized in that The liquid-to-solid ratio of the leaching is 2:1-8:1, the leaching time is 10-90 minutes, and the leaching temperature is 20-50°C.

9. The method according to claim 1, characterized in that: In step S4, the aging time is 2-4 hours; The temperature of the three-stage filter residue roasting is 400-600°C, and the roasting time is 1-3h.

10. The method according to any one of claims 1 to 9, characterized in that: In step S5, the first purifier is Ca(OH)2; the second purifier is Na2CO3; and the ratio of the added molar amount of the second purifier to the calcium ion is 1-1.3:1.

Citation Information

Patent Citations

  • Method for recovering carbon from aluminum electrolysis waste cathodes

    CN110407190A

  • A method for recovering carbon from waste cathodes in aluminum electrolysis

    CN110407190B

  • A method for recycling waste cathode carbon blocks from aluminum electrolysis

    CN111232947B

  • Resourceful treatment method for electrolytic aluminum overhaul slag

    CN117735578A

  • Method for electrolyzing waste and old cathode carbon block by comprehensive utilization of aluminum

    CN101480658A

Cited By

  • Method for treating overhaul slag by alkaline process and recycling

    CN121589112A